2011 IEEE International Conference on Information Reuse &Amp; Integration 2011
DOI: 10.1109/iri.2011.6009582
|View full text |Cite
|
Sign up to set email alerts
|

Clinical guidelines as decision support for referrals from primary care

Abstract: This work describes the use of clinical guidelines in public health care for decision support in a primary care record system. The clinical guidelines were used for decision support in primary care in order to improve the quality of electronic referrals to a hospital. Guidelines were developed by the specialists at the hospital, but the design and the development of the system was done in collaboration with general practitioners working in primary care. This paper sums up the findings from a study six months a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This observation may support the hypothesis, enabling an automated referral system may improve the communication gap, and reduce waiting time between the primary health center and the referred hospitals [ 6 ]. The evidence-based point-of-care instrument can thus be suggested that assist the process of filling out a referral template to reduce time and error [ 11 ] and helps to assist the referral follow-up [ 38 ]. However, further investigation is required to explore the barriers and facilitators for enhancing the quality of referral service and to deliver a fully functional and effective referral system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation may support the hypothesis, enabling an automated referral system may improve the communication gap, and reduce waiting time between the primary health center and the referred hospitals [ 6 ]. The evidence-based point-of-care instrument can thus be suggested that assist the process of filling out a referral template to reduce time and error [ 11 ] and helps to assist the referral follow-up [ 38 ]. However, further investigation is required to explore the barriers and facilitators for enhancing the quality of referral service and to deliver a fully functional and effective referral system.…”
Section: Discussionmentioning
confidence: 99%
“…Literature evidence suggests that assisting the referral decision process through decision support systems enables to: (I). aid the process of filling out a referral template [ 11 ], (II). provide an alternative recommendation using historical records [ 12 ], and (III).…”
Section: Introductionmentioning
confidence: 99%
“…Long waiting times for surgeries are also associated with higher risks of serious complications and death, especially among adults [ 16 , 17 ]. Amongst the research that has been done to improve referrals, positive decision support systems incorporating clinical guidelines and the collaboration of specialists have been found to be effective for general practice [ 18 ]. The reassurance of the necessity of the referral to the patient is also important because the non-attendance of some patients at surgery appointments is a major factor in prolonging waiting times for them and for other patients [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Long waiting times for surgeries are also associated with higher risks of serious complications and death, especially among adults (12,13). Amongst the research that has been done to improve referrals, positive decision support systems incorporating clinical guidelines and the collaboration of specialists have been found to be effective for general practice (14). Reassurance of the necessity of the referral to the patient is also important, because the nonattendance of some patients at surgery appointments is a major factor in prolonging waiting times for them and for other patients (15).…”
Section: Introductionmentioning
confidence: 99%